Multinational prospective cohort study of incidence and risk factors for central line-associated bloodstream infections over 18 years in 281 ICUs of 9 Asian countries - ROSENTHAL, VICTOR DANIEL; Yin, Ruijie; Rodrigues, Camilla Rodrigues; Myatra, Sheila Nainan; Divatia, Jigeeshu Vasishth; Biswas, Sanjay K; Shrivastava, Anjana Mahesh; Kharbanda, Mohit; Nag, Bikas; Mehta, Yatin; Sarma, Smita; Todi, Subhash Kumar; et al. (Wichtig Publishing Srl, 2023)
Background: Our objective was to identify central line (CL)-associated bloodstream infections (CLABSI) rates and risk factors (RF) in Asia. Methods: From 03/27/2004 to 02/11/2022, we conducted a multinational multicenter prospective cohort study in 281 ICUs of 95 hospitals in 44 cities in 9 Asian countries (China, India, Malaysia, Mongolia, Nepal, Pakistan, Philippines, Sri Lanka, Thailand, and Vietnam). For estimation of CLABSI rate we used CL-days as denominator and number of CLABSI as numerator. To estimate CLABSI RF for we analyzed the data using multiple logistic regression, and outcomes are shown as adjusted odds ratios (aOR). Results: A total of 150,142 patients, hospitalized 853,604 days, acquired 1514 CLABSIs. Pooled CLABSI rate per 1000 CL-days was 5.08; per type of catheter were: femoral: 6.23; temporary hemodialysis: 4.08; jugular: 4.01; arterial: 3.14; PICC: 2.47; subclavian: 2.02. The highest rates were femoral, temporary for hemodialysis, and jugular, and the lowest PICC and subclavian. We analyzed following variables: Gender, age, length of stay (LOS) before CLABSI acquisition, CL-days before CLABSI acquisition, CL-device utilization ratio, CL-type, tracheostomy use, hospitalization type, ICU type, facility ownership and World Bank classifications by income level. Following were independently associated with CLABSI: LOS before CLABSI acquisition, rising risk 4% daily (aOR = 1.04; 95% CI = 1.03-1.04; p < 0.0001); number of CL-days before CLABSI acquisition, rising risk 5% per CL-day (aOR = 1.05; 95% CI 1.05-1.06; p < 0.0001); medical hospitalization (aOR = 1.21; 95% CI 1.04-1.39; p = 0.01); tracheostomy use (aOR = 2.02;95% CI 1.43-2.86; p < 0.0001); publicly-owned facility (aOR = 3.63; 95% CI 2.54-5.18; p < 0.0001); lower-middle-income country (aOR = 1.87; 95% CI 1.41-2.47; p < 0.0001). ICU with highest risk was pediatric (aOR = 2.86; 95% CI 1.71-4.82; p < 0.0001), followed by medical-surgical (aOR = 2.46; 95% CI 1.62-3.75; p < 0.0001). CL with the highest risk were internal-jugular (aOR = 3.32; 95% CI 2.84-3.88; p < 0.0001), and femoral (aOR = 3.13; 95% CI 2.48-3.95; p < 0.0001), and subclavian (aOR = 1.78; 95% CI 1.47-2.15; p < 0.0001) showed the lowest risk. Conclusions: The following CLABSI RFs are unlikely to change: country income level, facility-ownership, hospitalization type, and ICU type. Based on these findings it is suggested to focus on reducing LOS, CL-days, and tracheostomy; using subclavian or PICC instead of internal-jugular or femoral; and implementing evidence-based CLABSI prevention recommendations.